1994
DOI: 10.1017/s1047951100002092
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of aortopulmonary windows with regard to their classification and morphogenesis

Abstract: We examined 25 heart specimens with aortopulmonary windows in order to review the variety of the lesion and its associated malformations. Unlike common arterial trunk, the aortopulmonary window involves a deficiency of the wall of the ascending aorta and that of the pulmonary trunk. The window was in proximal position in three specimens, intermediate position in three specimens, distal position in 16 specimens and was confluent in three specimens. The size of the window varied from 27 to 100% of the total leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Mori et al (9) identified three anatomical types of APW, namely proximal, distal and total. Ho et al (10) modified this classification system by adding the intermediate type. These classification systems have improved the selection of cases eligible for transcatheter repair with sufficient superior and inferior rims; we also utilised this classification system in our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Mori et al (9) identified three anatomical types of APW, namely proximal, distal and total. Ho et al (10) modified this classification system by adding the intermediate type. These classification systems have improved the selection of cases eligible for transcatheter repair with sufficient superior and inferior rims; we also utilised this classification system in our cases.…”
Section: Discussionmentioning
confidence: 99%
“…From an anatomic and physiologic standpoint, this defect resembles truncus arteriosus; however, unlike truncus arteriosus, two distinct semilunar valves are present. The size and location of the communication varies, and thus the defect has been classifi ed into various types [ 90 ]. The lesion can occur in isolation but in most cases is associated with other cardiovascular malformations (PDA, intracardiac communications, TOF, double outlet right ventricle, IAA).…”
Section: Aortopulmonary Window Anatomic Featuresmentioning
confidence: 99%
“…Mori et al [8] originally classifi ed APW into three subtypes based on proximal defects, distal defects, and total defects. To make this classifi cation more useful to interventional cardiologists, Ho et al [10] modifi ed it by adding a descriptor of superior and inferior rim tissue presence. Richardson et al [9] included an additional group of anomalous right pulmonary artery origin from the ascending aorta; however, based on standard nomenclature, this additional grouping is better defi ned as ascending aortic origin of one pulmonary artery and right ventricular origin of the other pulmonary artery.…”
Section: Classificationmentioning
confidence: 99%
“…Based on review and discussion of the several existing classifi cation schemes, the STS committee settled on fi ve APW subtypes: APW and interrupted aortic arch APW, type 1 proximal defect APW, type 2 distal defect APW, type 3 total defect APW, intermediate type The fi rst subgroup was created because of the oftenassociated condition of interrupted arch, which occurs with APW. This is the most common lesion occurring with APW; one study found it in 8 of 25 autopsy specimens [10]. In type 1 APW, or proximal defect, lesions are located directly above and next to the sinus of Valsalva, within a few millimeters of the semilunar valves.…”
Section: Classificationmentioning
confidence: 99%